Regulatory T Cells in Autoimmunity and Cancer: A Duplicitous Lifestyle - Hatzioannou, Aikaterini; Boumpas, Athina; Papadopoulou, Miranta; Papafragkos, Iosif; Varveri, Athina; Alissafi, Themis; Verginis, Panayotis (Frontiers in Immunology, 2021)
Regulatory T (Treg) cells, possess a strategic role in the maintenance of immune homeostasis, and their function has been closely linked to development of diverse pathologies including autoimmunity and cancer. Comprehensive studies in various disease contexts revealed an increased plasticity as a characteristic of Treg cells. Although Treg cell plasticity comes in various flavors, the major categories enclose the loss of FOXP3 gene, which is the master regulator of Treg cell lineage, giving rise to “ex-Treg” cells and the “fragile” Treg cells in which FOXP3 expression is retained but accompanied by the engagement of an inflammatory program and attenuation of the suppressive activity. Treg cell plasticity possess a tremendous therapeutic potential either by inducing Treg cell de-stabilization to promote anti-tumor immunity, or re-enforcing Treg cell stability to attenuate chronic inflammation. Herein, we review the literature on the Treg cell plasticity with lessons learned in autoimmunity and cancer and discuss challenges and open questions with potential therapeutic implications.